2011
DOI: 10.1080/00049158.2011.10676361
|View full text |Cite
|
Sign up to set email alerts
|

Fire frequency variation in south-eastern Tasmanian dry eucalypt forest 1740–2004 from fire scars

Abstract: An understanding of fire history is important in determining appropriate fire management regimes for biodiversity conservation in fire-prone ecosystems, such as the dry eucalypt forests of temperate Australia. We tested whether ring counts and evidence of fire in the stumps of felled eucalypts could be used to construct fire chronologies in the dry forests of south-eastern Tasmania. Given that the dates of fires derived from this method were consistent with other evidence of fire years, we constructed chronolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 50 publications
0
21
0
Order By: Relevance
“…A coincidence of change in land use with fire regime change and vegetation change has been observed elsewhere. In eastern Tasmania, fires became very infrequent with the disruption and destruction of Tasmanian Aboriginal land use between the beginning of the Black War in 1826 and the mid-1830s (von Platen et al, 2011). Between 1850 and 1990, fires were more frequent than under indigenous management (von Platen et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A coincidence of change in land use with fire regime change and vegetation change has been observed elsewhere. In eastern Tasmania, fires became very infrequent with the disruption and destruction of Tasmanian Aboriginal land use between the beginning of the Black War in 1826 and the mid-1830s (von Platen et al, 2011). Between 1850 and 1990, fires were more frequent than under indigenous management (von Platen et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…In eastern Tasmania, fires became very infrequent with the disruption and destruction of Tasmanian Aboriginal land use between the beginning of the Black War in 1826 and the mid-1830s (von Platen et al, 2011). Between 1850 and 1990, fires were more frequent than under indigenous management (von Platen et al, 2011). In New Zealand, there was a massive loss of forest associated with burning after the invasions of both Maori and Pakeha (Wardle, 1991;McGlone & Wilmshurst, 1999).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Broadly, there are two different approaches to reconstruction of past environments: environmental history, stemming from the humanities; and historical ecology from the sciences (Bowman 2002). The former relies on interpretation of historical documents and images Bowman 2002;Butzer and Helgren 2005;Mactaggart et al 2007;Gammage 2008) and the latter, environmental reconstructions using a range of proxies, the most important being dendrochronology (Banks 1982;von Platen et al 2011) and pollen and charcoal in sediments (Swetnam et al 1999;Whitlock and Larsen 2001;Turner and Plater 2004;Higuera et al 2005;Black et al 2007). These approaches are not mutually exclusive, indeed sometimes they motivate and inform each other, and can be effectively merged to provide more robust reconstructions of vegetation cover (Fensham 1989;Batek et al 1999;Benson and Howell 2002;Lunt 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Lowland grassland ecosystems and associated species are well adapted to frequent low level burning events, but are likely to be adversely affected by frequent high intensity fires (Lunt et al 2012). A study of the nearby Eastern Tiers showed that fire events have become less frequent in recent decades, and this has been driven in part by changing community attitudes to fires and the need to ensure protection of assets, including forest plantations (von Platen et al 2011).…”
Section: Governance Design For Conservation Program (23)mentioning
confidence: 99%